Buckling analysis of isotropic circular plate with attached annular piezoceramic plate - Syed Abu Bakar, Syed Noh; Abdalla, Mostafa M.; W. F., Waleed (Universiti Putra Malaysia, 2016)
A buckling analysis of an isotropic circular plate with piezoceramic annular plate attached to it is presented. The annular plate is attached at the circular plate edge so that the radius of the circular plate is the inner radius of the annular plate. The piezoceramic annular plate is used as the radial in-plane load source. The radial and hoop stresses are found to be depends on the radial throughout the annular region while constants throughout the circular regions. The governing equations is solved approximately using finite difference method. The solutions to be found to be in good agreement with results from FEM analysis. A parametric study also presented.